Phenotypic evaluation of contest cattle in Sorong Regency, Southwest Papua, Indonesia: morphometric traits and body condition score - Stefani F. Haryati; John A. Palulungan; Daniel Y. Seseray; Bernaddeta W. I. Rahayu; Rizki Arizona; Iriani Sumpe; Isti Widayati; Ditasari Amalia; Fitri A. Arief; Rizki Prasetya; Juni C. Dami; Riskayanti Riskayanti; Azchar P. P. Putra (Fakultas Peternakan Universitas Papua, 2026)
Phenotypic evaluation of contest cattle provides useful information for understanding body conformation and physical condition under field conditions, yet objective studies on contest-based cattle populations remain limited. This study aimed to evaluate morphometric traits and body condition score (BCS) of contest cattle from Sorong Regency, Southwest Papua, and to assess their variation according to district and sex, as well as the relationships among measured traits. Data were collected from 31 contest cattle originating from seven districts, consisting of 8 males and 23 females. The evaluated variables included chest girth (CG), body length (BL), withers height (WH), and BCS. Descriptive statistics were used to summarize the data, while sex and district effects were analyzed using the Mann–Whitney U test and Kruskal–Wallis test, respectively. Relationships among variables were examined using Spearman’s rank correlation, and principal component analysis (PCA) was applied to describe the multivariate structure of morphometric variation. The overall mean values were 152.60 ± 25.99 cm for CG, 108.26 ± 10.83 cm for BL, 116.58 ± 12.66 cm for WH, and 3.19 ± 0.54 for BCS. No significant differences were found between males and females for any variable. In contrast, district had a significant effect on WH and BCS, with the main difference occurring between Aimas and Mariat. Chest girth was positively correlated with BL (rho = 0.66, p < 0.001) and BCS (rho = 0.54, p < 0.01), indicating that this trait was the most informative single morphometric variable in the dataset. PCA showed that the first two principal components explained 87.55% of the total variation, representing general body size and vertical body structure. In conclusion, contest cattle in Sorong Regency exhibited greater phenotypic variation across districts than between sexes, and chest girth may serve as a practical indicator for field-based phenotypic evaluation of contest cattle.